LIABILITY OF EMPLOYEES CORRUPTION ERADICATION COMMISSION CAUSE EMBEZZLEMENT OF EVIDENCE - Ronald Hasudungan Sianturi; Ahmad Feri Tanjung; Rony Andre Christian Naldo (Universitas Labuhanbatu, 2024)
In carrying out law enforcement against suspected perpetrators of criminal acts of corruption, the CEC has the right to confiscate evidence. Regarding the evidence that has been confiscated, it is hoped that CEC employees will carry out their dutys to store the evidence. The legal fact is that one of the CEC employees embezzled evidence. This research discusses the duty of CEC employees to store confiscated evidence. In this regard, this research is focused on examining the liability of individual CEC employees for embezzling evidence. This research is prescriptive analytical in nature, using normative juridical methods, using a statutory approach, concept approach and case approach. The type of data used is secondary data. The results of the research concluded that according to the code of ethics, the responsibility of individual CEC employees for embezzling evidence is dishonorable dismissal. In terms of Criminal Law, the liability of individual CEC employees for embezzling evidence can be subject to a basic crime with a maximum threat based on the provisions of Article 374 of the Criminal Code, which is accompanied by additional penalties.Key Words: Employees, Embezzlement, Evidence.